Pelatihan dan Pendampingan bagi Pelaku usaha mikro dalam melakukan pembukuan sederhana di desa Botubarani kec. Kabila Bone Kab. Bone Bolango - Pratiwi Husain, Siti; Ali, Nurmillah N.; Suila, Muh. Adrifat; Abarang, Citra Vebryanti; Tumatar, Jihan Fahira (Jurnal Pengabdian Pada Masyarakat Indonesia, 2023)
Micro, Small and Medium Enterprises (MSMEs) are a very important economic sector in Indonesia's economic development. The MSME sector makes a significant contribution to economic growth, job creation, and economic equity. Therefore, we conducted socialization and simple bookkeeping training for MSMEs so that they can advance the income of the people in Botubarani Village. By conducting outreach to the people of Botubarani Village, so that they can introduce information about the importance of simple bookkeeping in this case is the traders in Botubarani Village. With the topic that we raise is "Training and Assistance for Micro Entrepreneurs in carrying out simple bookkeeping" as a Community Service program because it relates to the major we have chosen, namely accounting. Which in the program, the objects we chose were traders of Micro, Small and Medium Enterprises (MSMEs). This study aims to describe and analyze micro, small and medium enterprises (MSMEs) using simple bookkeeping in Botubarani Village